Health Locus of Control Is Associated With Physical Activity and Other Health Behaviors in Cardiac Patients. Issue 6 (November 2018) - Mercer, Darren A.; Ditto, Blaine; Lavoie, Kim L.; Campbell, Tavis; Arsenault, André; Bacon, Simon L.
Abstract : Purpose: Physical inactivity, smoking, and excessive alcohol use are well-recognized modifiable risk factors for cardiovascular disease (CVD), yet uptake of strategies to mitigate these poor health behaviors varies widely among patients with cardiovascular disease. Part of this variation may be explained by health locus of control (HLOC), defined as the extent to which individuals believe their health is a consequence of their own actions, chance, or the influence of others (eg, physicians). Methods: A total of 599 cardiac outpatients (30% female, 61.4 ± 9.4 y of age) completed the Multidimensional Health Locus of Control questionnaire and a structured health behavior questionnaire assessing physical activity, smoking, and alcohol use, at baseline and a 4-y follow-up. Relationships between health behaviors and HLOC were assessed cross-sectionally and longitudinally using general linear models and logistic regression models adjusting for medical and sociodemographic factors. Results: Higher Internal HLOC was found to be associated with higher levels of leisure time physical activity (LTPA) (β = .21, P = .0008), while lower Internal HLOC was associated with decreasing levels of alcohol consumption over time (β = .26, P = .03). Increasing Chance HLOC was related to lower levels of leisure time physical activity (β = −.15, P = .047) and increased likelihood of being a smoker (β = .10, P = .01), and increasing physician HLOC was associated with decreased likelihood of being a smoker (β = −.17, P = .01). Conclusions: Associations between HLOC and multiple health behaviors were observed in a large sample of cardiac outpatients. Results suggest that assessing and targeting HLOC beliefs of cardiac patients may be clinically relevant for behavior change in settings, such as in rehabilitation programs where behavior change is a goal. Abstract : In cardiac outpatients, higher internal health locus of control (HLOC) was associated with higher levels of leisure time physical activity. Higher Chance HLOC was associated with lower levels of leisure time physical activity, and increased likelihood of being a smoker. Higher physician HLOC was associated with decreased likelihood of being a smoker.